Prevalence of high-risk human papillomavirus infections and associated factors among women living with HIV in Shashemene town public health facilities, Southern Ethiopia - Tariku Megersa; Sisay Dango; Kebede Kumsa; Kebebew Lemma; Bikila Lencha (BMC, 2023)
Abstract Background Every year, large number of women are suffering from cervical cancer. Particularly women living with HIV are at high-risk of being suffered with it. Early testing of high-risk human papillomavirus infection can significantly reduce the incidence of cervical cancer. However, lack of early and regular testing has been identified as one of the major problems among risky populations. Methods Institutional-based cross-sectional study design was conducted among women living with HIV in Shashemene town public health facilities with a total sample size of 406 from February 1-March 30, 2022. Systematic random sampling technique was employed to select the study subjects. A structured questionnaire and checklist was used to collect data. The collected data were cleaned, coded, and entered into Epi-info version 7.2.5 and exported to statistical package for social science version 24 for analysis. Finally, bi-variable and multivariable logistic regression analyses were performed to identify determinants of high-risk human papillomavirus. Odds ratio with 95% confidence interval was used to test association between exposure and outcome under study and p-value < 0.05 was considered significant. Results The prevalence of high-risk HPV infections among study participant was 173(35.2%) with 95% CI (30.5%-40.1%). Prevalence of high-risk HPV type 16, 18 and other high-risk HPV types were 62(15.3%), 23(5.7%) and 58(14.3%), respectively. Having history of sexually transmitted infections [AOR = 3.120; 95% CI (1.977-4.923)], Endline CD4 count < 200 cells/mm3 [AOR = 3.072; 95% CI(1.009-9.350)], Endline HIV viral-load ≥ 50 copies/ml [AOR = 3.446; 95% CI(1.368-8.683)] and more than one-lifetime sexual partner [AOR = 2.112; 95% CI(1.297-3.441)] were significantly associated with high-risk HPV infections. Conclusion More than one third of women living with HIV had high-risk HPV. Having history of STI, low CD4 count, high viral load and multiple sexual partners were associated with high risk HPV. HIV positive women with these risk factors should be given special consideration in clinical and public health intervention.